PANDEMI COVID-19 DAN PRESTASI BELAJAR MAHASISWA PROFESI NERS - Christa Vike Lotulung; I Gede Purnawinadi (Fakultas Keperawatan, Universitas Klabat, 2022)
The COVID-19 pandemic has had a significant impact in various fields, especially in the world of education. The transformation of face-to-face learning activities to online certainly has consequences for student learning outcomes. This study analyzes the learning achievement of nursing students at the professional stage through a comparative GPA test in the semester before and during the pandemic. The research data were collected through a total sampling technique of 233 students' GPA at a private university in North Sulawesi. Data analysis for the comparative test used Mann Whitney non-parametric statistics because it did not meet the feasibility of the normality assumption. The results showed that there was a significant difference between the academic achievement of nursing professional students in the semester before pandemic (average GPA 3.20 with a standard deviation of 0.24) and during the COVID-19 (average GPA 3.55 with a standard deviation of 0.57) with a significant value of 0.000 (p value <0.05). The pandemic situation does not always have a negative impact on the learning process, a good concept of free learning through the application of technology in the learning process can also have a positive impact on students being free to study independently, even though the pandemic situation demands online learning activities. Institutions as education providers are expected to be able to develop a learning management system both face-to-face and online by increasing adequate facilities and resources in an effort to improve the quality of learning outcomes. KEYWORDS: Achievement Index, Nurse Profession Student, COVID-19 Pandemic Pandemi COVID-19 secara signifikan mempunyai dampak di berbagai bidang, terlebih khusus pada dunia pendidikan. Transformasi aktivitas pembelajaran tatap muka menjadi daring tentunya mempunyai konsekuensi terhadap hasil belajar mahasiswa. Penelitian ini menganalisis prestasi belajar mahasiswa profesi ners melalui uji komparatif IPK pada semester sebelum dan saat pandemi. Data penelitian dikumpulkan melalui teknik total sampling sebanyak 233 IPK maahasiswa pada salah satu perguruan tinggi swasta di Sulawesi Utara. Analisis data untuk uji komparatif menggunakan statistik non parametrik Mann Whitney karena tidak memenuhi kelayakan asumsi normalitas. Hasil penelitian menunjukkan terdapat perbedaan yang signifikan antara prestasi belajar mahasiswa profesi ners pada semester sebelum pandemi (rata-rata IPK 3,20 dengan standar deviasi 0,24) dan saat pandemi COVID-19 (rata-rata IPK 3,55 dengan standar deviasi 0,57) dengan nilai signifikan 0,000 (p value < 0,05). Situasi pandemi tidak selalu berdampak negatif terhadap proses pembelajaran, konsep merdeka belajar yang baik melalui penerapan teknologi dalam proses pembelajaran dapat memberikan dampak yang positif juga terhadap para mahasiswa dalam bebas belajar secara mandiri, meskipun situasi pandemi menuntut kegiatan pembelajaran secara daring. Institusi sebagai penyelenggara pendidikan diharapkan mampu mengembangkan sistem manajemen pembelajaran baik tatap muka maupun daring dengan meningkatkan fasilitas dan sumber daya yang memadai dalam upaya meningkatkan kualitas hasil pembelajaran. Kata kunci: Indeks Prestasi, Mahasiswa Profesi Ners, Pandemi COVID-19